A mobile cache model with semantic locality. (21st August 2007) - Wei, Guiyi; Shi, Hanxiao; Ling, Yun
Restricted by wireless communication technology and mobile computing environment, it is difficult to improve the efficiency of the programs that resided in mobile end. To solve this problem, the cache mechanism is a major and effective method. In this paper, we propose an application-oriented semantic cache model. It establishes a semantic-associated rules base according to the knowledge of application domains, makes use of the semantic locality for data pre-fetching, and adopts a two-level LRU algorithm for cache replacement. Several experiments demonstrate that the semantic-driven cache model can achieve higher hit ratio than traditional cache models.